The Burdensome and Depressive Experience of Caring: What Cancer, Schizophrenia, and Alzheimer’s Disease Caregivers Have in Common - Tsangari, Haritini; Charalambous, Andreas; Papastavrou, Evridiki (My University, 2012)
Background: Family members of patients with chronic illnesses experience distress as a result of caregiving roles, which can be manifested as burden and depression, but cross-disease studies on how caring is experienced are limited. Objective: The present study was designed to examine the burden and psychiatric morbidity in the form of depression experienced by Cypriot families caring for a relative with one of the following: cancer, Alzheimer’s disease, or schizophrenia. Methods: This study was cross-sectional, descriptive, and correlational. A total of 410 caregivers were recruited from the community. The research instruments included the Greek version of the Burden Interview and the Center of Epidemiological Studies–Depression Scale. Descriptive statistics, 1-way analysis of variance, and post hoc Tukey pairwise comparisons were used to examine significant differences between the 3 groups. Results: The results indicate a high level of burden and depression among all caregivers. Significant differences (P < .001, F = 26.11) between the 3 caregiving groups were detected in terms of burden, with the highest reported for Alzheimer’s disease caregivers. One-way analysis of variance showed significant differences (P = .008, F = 4.85) between the 3 caregiving groups in terms of depression, with the highest depression levels being for cancer caregivers. Conclusions: The findings increase our understanding about burden and emotional well-being in family caring for relatives with cancer and other chronic illnesses. Implications for Practice: The findings may be useful for health professionals to plan intervention strategies focusing on each domain of burden. The lessons learned from the caregiving role of family caregivers of patients with Alzheimer’s disease or schizophrenia can be used to improve the caregiving process of patients with cancer.
Keywords: Alzheimer's disease; Cancer; Caregivers; Depression; Family; Schizophrenia